2010
DOI: 10.2215/cjn.05660809
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy in Dialysis Patients

Abstract: Conclusions: Evidence on pregnancy in dialysis is heterogeneous; however, the growing number of reports worldwide and the improving results suggest that we should reconsider our counseling policy, which only rarely includes pregnancy in dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
1
16

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 26 publications
(26 reference statements)
2
81
1
16
Order By: Relevance
“…Although prematurity is very likely, a large proportion do progress to a satisfactory duration. Other studies from the recent era report a median GA of 31-33 weeks (2,6,9,10,20), with superior GA in patients treated with nocturnal hemodialysis (16,18). Most infants born were of low BW (,2500 g), which correlated with prematurity, although a large proportion of babies were on or below the 10th centile of weight for GA. Our median BW was similar to that in other recent studies, which reported median or mean BW ranging from 1483 to 1765 g (6)(7)(8)(9)(10)20), but it remains substantially less than the mean BW (6 SD) of 2417.56657 g reported in pregnancies managed with nocturnal hemodialysis (16).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Although prematurity is very likely, a large proportion do progress to a satisfactory duration. Other studies from the recent era report a median GA of 31-33 weeks (2,6,9,10,20), with superior GA in patients treated with nocturnal hemodialysis (16,18). Most infants born were of low BW (,2500 g), which correlated with prematurity, although a large proportion of babies were on or below the 10th centile of weight for GA. Our median BW was similar to that in other recent studies, which reported median or mean BW ranging from 1483 to 1765 g (6)(7)(8)(9)(10)20), but it remains substantially less than the mean BW (6 SD) of 2417.56657 g reported in pregnancies managed with nocturnal hemodialysis (16).…”
Section: Discussionmentioning
confidence: 93%
“…However, given prolonged waiting times for organs, this may occur after the reproductive years have passed. With studies such as ours demonstrating improved outcomes for women with CKD who commence dialysis in pregnancy, as well as the growing body of evidence regarding intensive dialysis regimens to improve outcomes (6)(7)(8)(9)(10)16), there may be a shift in the way women are counseled regarding pregnancy on dialysis, toward a less discouraging attitude (2). This may provide an avenue for motherhood in women who otherwise may not have an opportunity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Este fenómeno se acentúa a medida que disminuye la función renal y en pacientes con ERC en etapas 4 y 5, 75% de los RN son pequeños para la edad gestacional y 100% de los partos son prematuros, con un promedio de edad gestacional de 32 semanas, lo cual es bastante similar a nuestros resultados. En la serie de Piccoli, la proteinuria mayor a 1 g/día se correlacionó con el requerimiento de cuidados neonatológicos intensivos y la hipertensión arterial con el parto prematuro 10,11 .…”
Section: Discussionunclassified